Evaluation of post-discharge engagement for emergency department patients with opioid use history who received telehealth recovery coaching services - Dennis P. Watson; Peter Phalen; Spencer Medcalf; Sarah Messmer; Alan McGuire (BMC, 2023)
Abstract Background In recent years, emergency departments (EDs) across the nation have implemented peer recovery coach (PRC) services to support patients who use opioids. The majority of such interventions discussed in the literature follow an in-person modality where PRCs engage patients directly at the ED bedside. However, the use of telehealth services in EDs is becoming more popular. These services connect PRCs with ED patients in real-time via secure communications technology, and very little is known about the service- and clinical-based outcomes with which they are associated. The current study sought to assess factors associated with successful post-discharge follow-up of patients with a history of opioid use who received PRC telehealth services while in the ED. Method Data come from records for 917 patients who engaged with a telehealth PRC one or more times (1208 total engagements) at 1 of 13 EDs within the same health system. A multilevel Poisson regression model was used to assess the degree to which variables predicted successful post-discharge follow-up, defined as the number of times a PRC successfully spoke with the patient each month after ED discharge. Results At least one follow-up was successfully completed by a PRC for 23% of enrolled patients. Significant predictors of successful follow-up included patient employment at baseline (Incidence Rate Ratio [IRR]: 2.8, CI: 2.05-3.9), living in a rural area (IRR: 1.8, CI: 1.04-3.2), PRC provision of referrals (IRR: 1.7, CI: 1.2-2.2), number of ED encounters in the previous 365 days (IRR: 0.99, CI: 0.98-0.99), and duration of the initial PRC telehealth interaction (IRR: 0.87, CI: 0.85-0.88). Conclusion Given that relationship development is a key tool in the PRC profession, understanding successful follow-up associated with telehealth engagement has unique importance. The results have potential utility for planning and implementing peer telehealth services in EDs and other locations, which is needed for the development of the PRC profession and the likely expansion of peer telehealth services.